On some inequalities for polynomials - Timan, M. F. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove the equivalence between analogs of the Paley and Nikol’skii inequalities for any orthonormal system of functions and for almost periodic polynomials with arbitrary spectrum.